Wound Healing Metabolites as the Right Medicines for the Therapy of Diseases Arising due to the Collapse of Chemo-Surveillance - Ming C. Liau; Christine Liau Craig (Current Overview on Disease and Health Research Vol. 1, 2022)
The objectives of this study were to explore the mechanisms of wound healing, and to seek wound heading metabolites as the right medicines for the therapy of diseases arising due to the collapse of chemo-surveillance, most of which were untreatable. Wound healing and cancer evolution have a lot in common, and Progenitor Stem Cells (PSCs) are a big part of it. Proliferation and Terminal Differentiation (TD) of PSCs are required for wound healing. Biological and immunological responses are triggered by wounds. The biological response involves the release of Arachidonic AcId (AA) from membrane bound phosphatidylinositol for the synthesis of ProstaGlandins (PGs) which are active Differentiation Inducers (DIs). AA and PGs are DIs good for wound healing. Immunological response prompts the production of Tumor Necrosis Factor (TNF), which is also named cachectin after its effect to cause cachexia symptom. Because TNF can cause increased urine excretion of low molecular weight metabolites, causing wound healing metabolites to be lost, cachexia is a poor sign for wound healing. As a result, chemo-functionality surveillance’s is critical in determining the effectiveness of wound healing. If the chemo-surveillance system works as well as it does in healthy persons, a wound can always heal without leaving a scar. But if the functionality of chemo-surveillance has been damaged due to pathological conditions causing cachexia symptom, then healing of wound may be impaired to result in ugly scar, or even worse dementia in the case of brain damage unable to heal, or tissue fibrosis in the case of Covid-19 infection, or the most feared case of cancer. Ugly scar in visible surface is a medical concern, particularly with respect to cosmetic surgery and regeneration medicine. The study of wound healing is helpful to heal wound with no scar and to search for a more appropriate strategy of therapy against diseases arising due to the collapse of chemo-funtionality.